Mind the Gap: Creative Writing Comes to France - Charles HOLDEFER (E-REA)
The difference between research and creative writing is sometimes cast as an opposition between head and heart. On the one side, an objective intellect; on the other, a sensibility in the grip of inspiration. This cliché is ripe for debunking. Scholars frequently refer to their passion for a subject and their quest to make an original contribution. Artists often describe their work as painstaking and methodical, a product of revision with an awareness of precedents. Differences of convention can sometimes obscure a shared enterprise in literature.This article addresses my personal experience as an American writer from an MFA program who has adapted to the French university system, where the “head and heart” dichotomy remains largely unquestioned. The reputed rigor of the concours and the supposed spontaneity of workshop criticism offer a cultural contrast. But this contrast, I argue, is not as stark as it appears.